Quelle recherche in-disciplinée la complexité des langues exige-t-elle? - Eloy, Jean-Michel (My University, 2011)
The development of sociolinguistics is first examined here through successive issues of Encyclopedia Universalis. We then consider "crossings" between different fields: diachronical linguistics, variation, language boundaries, glottogenesis or language building, on the basis of which we show that sociolinguistics always poses truly linguistic questions, i.e. questions about the very definition of languages. Finally, we bring to bear the case of close languages, wherein many aspects of the above questions are brought to light. All in all, this paper assumes that heterogeneity in sociolinguistics is due to its original position amongst language sciences: its opening to new problems can be based on its theoretical foundations, and makes it a sort of avant-garde means of exploration into language complexity.